METODE KB PADA IBU MENYUSUI - Jualianawati, Tinta; Amir, Eka Fitri; Huzaima, Huzaima; Aditya, Aditya (UKInstitute, 2022)
Breast milk is the best life fluid that is needed by babies. Breast milk contains various substances that are important for the growth and development of babies and according to their needs. The causes that affect the smooth production of breast milk are factors such as maternal food intake, peace of mind and peace of mind, use of contraception, breast care, rest, work, and drugs. Babies who don't get enough breast milk are at risk of developing hypoglycemia and slower weight gain than babies who are getting enough breast milk. The purpose of this service is to determine the selection of family planning methods for breastfeeding mothers in order to increase their insight and knowledge and to be able to delay and distance the child's age. By using the question and answer method and discussion. The existence of hormonal contraception, especially injectable contraception, is the contraceptive that is most in demand by family planning acceptors, which is the safest, practical, and does not need to be reminded every day. Injectable contraceptives that can be given to breastfeeding mothers are progestin-based injections.